THE IMPORTANCE OF DEVELOPING CREATIVITY IN STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the importance of developing creativity in students, the formation of teachers' creative abilities and their role in their work. It discusses the creative qualities of a teacher. It discusses creative thinking in the educational process, the creation of various ideas, and actions to increase the effectiveness of the lesson through discussions.